Impact of the National Drug Price Negotiation policy on the price, usage, and affordability of anticancer medicines in Shandong Province, China - Yaqun Sun; Yan Qiang; Yongxuan Duan; Yan Song; Yan Song (Frontiers in Public Health)
ObjectiveIn order to reduce the price and increase the accessibility of innovative medicines, China has implemented the National Drug Price Negotiation (NDPN) since 2016. Anticancer drug is the largest category of NDPN and the number continue to increase. This study evaluated the impact of this policy on the price, utilization rate and affordability of anticancer drugs based on the experiences of Shandong province.Methods25 anticancer drugs were included in this study involved the NDPN in the year 2018 and 2019. Data on prices and utilization of the policy related drugs from 2017 to 2022 were collected from Shandong Province, using an adaptation of the WHO/HAI methodology. Prices were measured as Median Price Ratio (MPR). Usage was measured as Defined Daily Doses (DDDs). Affordability was measured as days of daily per capita disposable income required for the cost of 1 month’s treatment. The Mann–Whitney U test was used to estimate the significance of the difference in the change in the MPRs before and after the negotiation.ResultsThe data of this study come from 42 key monitoring medical institutions in Shandong Province, including 31 tertiary medical institutions and 11 secondary medical institutions. There has been a significant reduction in the MPR following NDPN, with a median MPR of 0.57 in 2022, and the prices of anticancer medicines were generally lower than IPR. During the period from 2017 to 2022, the total usage of the 25 negotiated medicines continued to rise. With the implementation of negotiation policy, the average number of days of disposable income per capita required for 1 month of medicine costs changed from 104 days to 36 days and 256 days to 80 days for urban and rural residents, respectively. The affordable proportion of anticancer medicines is still not high.ConclusionThe NDPN policy has reduced the prices of anticancer drugs and greatly improved their affordability. More attention should be paid to improve the affordability to the rural and the poor patients. It is essential to encourage the research and development of high-quality generic drugs to strengthen reasonable market competition, as well as improve the multi-tiered medical security system.